Cryptocurrency as a Tool for Financial Inclusion: Legal and Sociological Perspectives - MW Lasut, Meiske; Mesra, Romi (Labor Program Studi Pendidikan Sosiologi, 2023)
This study aims to analyze the pattern of cryptocurrency regulation in various jurisdictions and identify factors that influence its adoption as a financial inclusion tool. The method used is a comparative analysis of regulatory policies in various countries and a literature study related to the socio-economic impacts and barriers to cryptocurrency adoption. The results of the study show significant variations in regulatory approaches between developed and developing countries, where digital infrastructure factors, financial literacy, and structural barriers are the main determinants of the level of cryptocurrency adoption in each region.